Modelo espacial de la biomasa aérea de la cuenca del Putumayo en el noreste de la Amazonía Peruana - Angulo Cainamari, Christian Adan (2024)
The present research determined a spatial model of the aerial biomass of the Putumayo watershed in the northeastern Peruvian Amazon, using field data from 41 plots installed in the watershed for Peru and spectral data from the study area. Obtaining that the aerial biomass in the field varied from 41.6 - 513.2 Mg/ha with an average of 247 Mg/ha ± 15.7 standard error and a coefficient of variation of 41.4%, being the flooded palm forest the vegetation type with the highest aerial biomass obtaining an average of 291 ± 18, CV 20.5%. The middle part of the Putumayo basin presented a greater amount of aerial biomass with an average of 300.6 ± 32.4, CV 34.1% (164.4 - 513.2 Mg/ha). For the spatial model the bioclimatic variable of precipitation of the driest month (BIO 14) presented a greater import for the model, an R2 = 0.83 and RMSE = 53.5 Mg/ha was observed and the Wilcoxon statistical test determined a p-value = 0.36, showing a similarity between the aerial biomass estimated in the field and the one estimated by the spatial model. The conclusion is that the Putumayo basin has a high amount of aerial biomass